Necessity and adequacy of near-source factors for not-so-tall fixed-base buildings - Alhan, Cenk; SÜRMELİ, MELİH (Springer, 233 Spring St, New York, Ny 10013 USA, 2015)
Nonlinear response history analyses and use of strong ground motion data including near-field effects has become a common practice in both performance based design of tall buildings and design of base-isolated buildings. On the other hand, ordinary buildings are commonly analysed via response spectrum analysis following the rules of conventional seismic codes, most of which do not take near-field effects into account. This study evaluates the necessity and the adequacy of near-source factors for ordinary fixed-base buildings that are not specifically classified as tall, by comparing dynamic responses of 3, 8, and 15-story benchmark buildings obtained via (1) linear time history analyses using 220 record components from 13 historical earthquakes and 45 synthetic earthquake records of different magnitudes and fault distances and (2) response spectrum analyses in accordance with the Turkish Earthquake Code 2007 -representing seismic codes not taking near-field effects into account- and the Uniform Building Code 1997 which takes near-field effects into account via near-source factors that amplify design response spectrum. It is shown that near-source factors are crucial for the safe design of not-so-tall ordinary fixed-base buildings but those defined in UBC97 may still not be adequate for those located in the vicinity of the fault.
Keywords: Near-field effects; Near-source factors; Low-rise buildings; Mid-rise buildings